REVOLUSI KESEJAHTERAAN: MENUJU PERTUMBUHAN EKONOMI INKLUSIF DAN PENURUNAN TINGKAT KEMISKINAN DI KALIMANTAN TENGAH - Risdayanti Risdayanti; Alexandra Hukom (BORJUIS: JURNAL OF ECONOMY, 2024)
Central Kalimantan, with its abundant natural resources, is still trapped in a cycle of poverty. A new strategy is needed to encourage inclusive and sustainable economic growth, while reducing poverty levels in this region. The aim of this research is to determine the factors that influence inclusive economic growth in Central Kalimantan. The research method used is quantitative using a path analysis approach. The research results show that variable X1 has a t-statistic value of 3,363 with a Prob value. (significance) of 0.0014 (<0.05), it can be concluded that variable X1 has a direct influence on the intervening variable Y1, meaning that the human development index directly influences the level of inclusive economic growth in Central Kalimantan. Meanwhile, the variable X2 has a t-statistic of -1.551 with a prob value. (significance) of 0.1268 (>0.05), this value is more than 0.05, meaning that labor absorption has no direct effect on inclusive economic growth in Central Kalimantan. Variable Y1 (Intervening) has a t-statistic value of 5.622 with a Prob value. (Significance) is 0.0000 (<0.05), so it can be concluded that variable Y1 (Intervening) has a significant or direct effect on the dependent variable. Furthermore, the Adjusted R-squared value is 1.159, so it can be concluded that the contribution of the variables X1, X2 & Y1 (Intervening) to the dependent variable Y2.